Rapid optical thermal processing of silicon solar cells - Schindler, R.; Reis, I.; Wagner, B.; Eyer, A.; Lautenschlager, H.; Schetter, C.; Warta, W.; Hartiti, B.; Slaoui, A.; Muller, J.C.; Siffert, P. (IEEE Twenty Third Photovoltaic Specialists Conference, 1993, 1993)
Rapid thermal processing has been applied to silicon solar cell technology by using large area optical heaters which are suitable for continuous processing. All important processing steps to make solar cells have been realized by RTP methods: spin-on emitters, Al-BSF with low recombination rates and passivating oxides. The influence of the RTP has been investigated for the single steps as well as for a combination of several RTP steps. Although the individual process steps are not optimized yet, solar cells of 16.6% efficiency were fabricated.< >